Pulmonary mucormycosis: A case report and review of the literature - WANG, XI-MING (Oncol Lett, 2016)
The current study reports the case of a 15-year-old male who presented to The First Affiliated Hospital of Soochow University (Suzhou, Jiangsu, China) with a 3-day history of anergy and epistaxis. The patient was diagnosed with T-cell acute lymphoblastic leukemia according to the results of a bone marrow examination and received chemotherapy. During the agranulocytosis period, the patient developed pneumonia of the right upper lung (RUL). Once complete remission was achieved, the patient underwent a lobectomy of the RUL, together with amphotericin B therapy, following the confirmation of pulmonary mucormycosis by the histopathological results. The patient experienced 12 months of uneventful follow-up post-surgery.